2006
DOI: 10.1021/jm060272y
|View full text |Cite
|
Sign up to set email alerts
|

C-(4,5,6-Trimethoxyindan-1-yl)methanamine:  A Mescaline Analogue Designed Using a Homology Model of the 5-HT2A Receptor

Abstract: A conformationally restricted analogue of mescaline, C-(4,5,6-trimethoxyindan-1-yl)-methanamine, was designed using a 5-HT(2A) receptor homology model. The compound possessed 3-fold higher affinity and potency than and efficacy equal to that of mescaline at the 5-HT(2A) receptor. The new analogue substituted fully for LSD in drug discrimination studies and was 5-fold more potent than mescaline. Resolution of this analogue into its enantiomers corroborated the docking experiments, showing the R-(+) isomer to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Extending previous work on indanalkylamine analogues of DOM (15), [197] a conformationally constrained 1-aminomethylindan analogue (44) of mescaline (4) was recently designed [200] using the aforementioned in silico activated 5-HT 2A homology model. [137] Analogue 44 showed a threefold increase in affinity (K i = 130 nm), and a twofold increase in stimulating IP 3 accumulation (EC 50 = 6100 nm) compared to mescaline (4, K i = 360 nm; EC 50 = 11 300 nm).…”
mentioning
confidence: 99%
“…Extending previous work on indanalkylamine analogues of DOM (15), [197] a conformationally constrained 1-aminomethylindan analogue (44) of mescaline (4) was recently designed [200] using the aforementioned in silico activated 5-HT 2A homology model. [137] Analogue 44 showed a threefold increase in affinity (K i = 130 nm), and a twofold increase in stimulating IP 3 accumulation (EC 50 = 6100 nm) compared to mescaline (4, K i = 360 nm; EC 50 = 11 300 nm).…”
mentioning
confidence: 99%
“…Next, they synthesized a more conformationally restricted compound, which maintains the embedded mescaline structure in a low-energy conformation and docked this molecule to the 5-HT 2A homology. And it also showed that the amine-bearing side chain adopts a gauche orientation upon binding to the receptor [16]. So, we can conclude that conformation I is more favorable.…”
Section: Conformation Analysismentioning
confidence: 70%
“…Calculations on the docked conformation indicate that this form is higher in energy than that in which the side chain is in the anti conformation. Insight was gained from investigations on C-(4,5,6trimethoxyindan-1-yl)methanamine, in which the side chain is considerably constrained by covalent linkage to the benzene ring 62. The compound possessed threefold higher affinity and potency than mescaline, as well as equal efficacy at the 5-HT 2A receptor.…”
Section: Receptor Bindingmentioning
confidence: 99%